Matematyka
pezet445
2017-09-26 18:18:15
4/216 4. Opuść nawiasy, a następnie zredukuj wyrazy podobne. a)- b)- c) -6x-(3x-y)+4(-2x+y) d) 3(x2-2xy+2y2)-(3x2-4xy-y2) e) (6m-2mn+n)-4(1,5m-3n) f) -6(1/3a2-1/2a+2)-4(0,75a-0,5a2)
Odpowiedź
natus2107
2017-09-26 20:13:02

c)  -6x-(3x-y)+4(-2x+y) =  -6x-3x+y -8x+ 4y = - 17x + 5y d) 3(x²-2xy+2y²)-(3x²-4xy-y²) = 3x² - 6xy + 6y² - 3x² + 4xy + y²=  - 2 xy + 7y² e) (6m-2mn+n)-4(1,5m-3n) = 6m - 2mn + n - 6m + 4n = - 2mn + 5n f) -6(1/3a²-1/2a+2)-4(0,75a-0,5a²) = - 2a²  - 3a - 12 - 3a + 2a² = - 6a - 12

Dodaj swoją odpowiedź